The The Effect of Competence, Job Placement and Job Satisfaction on Employee Performance at the Regional Office VII BKN - Sartika, Lusi; Fatimah, Fatimah; Asiati, Diah Isnaini (International Journal of Business, Management and Economics, 2022)
This study aims to determine and analyze 1) the effect of competence, job placement and job satisfaction on employee performance at the Regional Office VII BKN, 2 ) the effect of competence on employee performance at the Regional Office VII BKN, 3) the effect of job placement on employee performance at the Regional Office VII BKN and 4) Job Satisfaction on employee performance at Regional Office VII BKN. The object of research is the employee at the Regional VII BKN office. The research method is associative using primary data. The population of this study was 140 employees, the sample selection technique used in this study was a probability sampling technique with a cluster random sampling method obtained through the formula of Isaac and Michael as many as 100 employees. The analysis technique used is multiple linier regression analysis. The results showed tha 1) simultaneously competence, job placement and job satisfaction had a significant effect on employee performance at Regional Office VII BKN, 2) competence had a significant effect on employee performance at Regional Office VII BKN, 3) job pacement had a significant effect on employee performance. At Regional Office VII BKN 4) job satisfaction has a significant effect on employee performance at Regional Office VII BKN